Effectiveness of Ultrasound Modality In Carpal Tunnel Syndrome (CTS) Patients: Literature Review - Putri Maharani, Aisya; Alya Syahda, Dinda; Nur Alpiah, Dini (Worldwide Research Publishing, 2024)
Carpal Tunnel syndrome is the most common problem in young to elderly people with a preval_ence of 20.3%. in Indonesia. Ultrasound is non-invasive and easy to apply without causing side effects and can speed up the healing of damaged tissue with a warming effect. This research aims to determine the effectiveness of ultrasound modality for carpal tunnel syndrome sufferers. Literature review research was carried out using the PICO search in the Google Scholar database. There were 5 journals that met the criteria and showed the results that Ultrasound carried out for 15 minutes per session with an intensity of 1.0 W/cm2, frequency of 1 MHz, 15 minutes per session, 5 times a week for 6 weeks, gave better results in eliminating pain and functional activity. Ultrasound modality therapy provides significant effectiveness p<0.001 in reducing pain, reducing median nerve inflammation and helping nerve recovery by stimulating regeneration.